2014
DOI: 10.1177/0898264314525666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Speed of Processing Training Among Older Adults With Heart Failure

Abstract: Results indicate that speed of processing training may improve everyday cognitive performance among older adults with HF. Future studies should investigate the longitudinal effects of cognitive training with HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…Fortunately, cognitive training, specifically speed of processing training, improves on-road driving performance (Roenker et al, 2003); prolongs driving mobility (Edwards et al, 2009c); reduces rates of driving cessation (Edwards et al, 2009a); and reduces at-fault motor vehicle crash involvement (Ball et al, 2010). This intervention has shown potential efficacy in HF as well (Ellis et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, cognitive training, specifically speed of processing training, improves on-road driving performance (Roenker et al, 2003); prolongs driving mobility (Edwards et al, 2009c); reduces rates of driving cessation (Edwards et al, 2009a); and reduces at-fault motor vehicle crash involvement (Ball et al, 2010). This intervention has shown potential efficacy in HF as well (Ellis et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that training that focuses specifically on cognitive speed of processing can be effective (M. L. Ellis, Edwards, Peterson, Roker, & Athilingam, 2014). Evidence suggests that training that focuses specifically on cognitive speed of processing can be effective (M. L. Ellis, Edwards, Peterson, Roker, & Athilingam, 2014).…”
Section: Skill and Agingmentioning
confidence: 99%
“…The physical and cognitive demands of the illness become so complex that cardiac patients can perform fewer and fewer cognitively challenging tasks over time [10]. Cognitive impairment in cardiac patients has been associated with (a) reduced likelihood to make appropriate self-decisions, (b) decreased self-care, (c) reduced ability to make medical decisions, (d) poor compliance with medication and (f) increased associated costs [11,12]. Overall, these affect the day to day functional capacity of such patients and reduce their health-related Quality of Life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…Further, data from Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) study also revealed that retraining of speed of processing ability helps improve everyday cognitive performance [11]. Additionally, computerized plasticity based cognitive training intervention called Brain Fitness showed improved performance on memory [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation